LNA A 1.9 GHZ low noise amplifier - Moreno-Rubio, Jorge Julián; Hernández-Rangel, Libardo Enrique (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2006)
This paper shows the design, the simulation, and the layout from a low noise amplifier (LNA), designed with and approximate band from 25 to 80 MHz. The design results of the matching neworks are shown, its noise figure, its available and transduced gain according to its non lineal model (TOM), the DC network, crash inductors and matching capacitors with the large impedance transmission lines.